VD_FINDINFO Décision / 2011 / 647 vom 31. August 2011 - VD Tribunal cantonal (2011)
DÉCISION D'IRRECEVABILITÉ, VALEUR LITIGIEUSE, MOYEN DE DROIT CANTONAL | 308 al. 2 CPC (CH), 320 CPC (CH), 398 al. 5 CPP (CH), 403 al. 1 let. a CPP (CH)